A Study on Writing Ability Differences between Male and Female Students in Describing People - Sri Wulandari; Edi Trisno (Universitas Negeri Padang, 2020)
Gender is considered to be one of the distinguishing levels of students' success in language acquisition including writing ability. Descriptive text is one of text types that should be mastered by English Language and Literature Departments students of Universitas Negeri Padang. This study intends to investigate and analyzed male and female students’ writing ability differences in writing descriptive text about describing people, from the aspects of generic structure, language features, vocabulary, and mechanics. This research conducted by using descriptive research and using a test as instrument collected from 26 male and 26 female students of English department, Universitas Negeri Padang. Moreover, the researcher used quantitative data analysis. The result show that male students and female students’ writing ability in describing people at the same category which is good but the mean score were slightly different. The male students scored 2,92 (good) and the female students scored 3,09 (good). Moreover, from all of the aspects assessed female students got higher score rather than male students. In identification the male students scored 3,15 and the female students scored 3,35. In description the male students scored 3,08 and the female students 3,35. In language features the male students scored 2,65 and the female students scored 2,69. In vocabulary the male students scored 2,85 and the female students 3,15. Last, the male students scored 2,88 and the female students scored 3,04 in mechanics.